1995
DOI: 10.1074/jbc.270.11.5695
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Domains of Interaction of p40 with Both p47 and p67 of the Neutrophil Oxidase Complex Using the Two-hybrid System

Abstract: The superoxide-generating NADPH oxidase complex in phagocytic cells is constituted of a heterodimeric flavocytochrome b and cytosolic factors, p67phox, p47phox and p40phox as well as a small G protein Rac (for review, see Refs. 1-3). A truncated form of the p40phox cDNA was isolated by a two hybrid screen of a B lymphocyte library using a full length clone of p47phox as target. This truncated form of p40phox consisting of the Src Homology 3 (SH3) domain to the 3' stop codon was also shown to interact with p67p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
1
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 26 publications
6
75
1
2
Order By: Relevance
“…This suggests that a cytoskeleton docking site for p40 phox could become available after PMA stimulation. A potential docking site is p47 phox , because an interaction between p40 phox and phosphorylated p47 phox has been described [36]; an alternative potential docking site is coronin, as Grogan et al [37] showed that p40 phox binds directly to this protein.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a cytoskeleton docking site for p40 phox could become available after PMA stimulation. A potential docking site is p47 phox , because an interaction between p40 phox and phosphorylated p47 phox has been described [36]; an alternative potential docking site is coronin, as Grogan et al [37] showed that p40 phox binds directly to this protein.…”
Section: Discussionmentioning
confidence: 99%
“…The O 2 À generating NADPH oxidase is a multicomponent system consisting of a membrane-bound flavocytochrome b 558 (composed of two subunits, p22 phox and gp91 phox ) [19] and four cytosolic factors, p47 phox , p67 phox , p40 phox and the small G protein, rac 2 [20]. These cytosolic proteins interact with each other [21,22], with rac [23,24] and with the flavocytochrome [25][26][27] through a number of Src homology 3 (SH3), proline-rich, tetratricopeptide repeat, and PC motifs. Using immunological and matrixassisted laser desorption ionisation-time of flight analysis (MALDI-TOF), the presence of homologous proteins to p67 phox and p47 phox were found in insect hemocytes [6] further strengthening the similarities between the oxidative burst pathways in the two cell types.…”
Section: Introductionmentioning
confidence: 99%
“…This is the minimum complex required to generate the microbicidal superoxide anion. An additional cytosolic factor, p40pho", is known also to associate with the NADPH oxidase complex (Wientjes et al, 1993), although its regulatory roles remain uncertain.P40PhoX, p47phox, and p67phoX each contain Src homology 3 (SH3) domains, which mediate multiple associations with proline-rich targets within the NADPH oxidase complex (Fuchs et al, 1995;de Mendez et al, 1996). These domains are also present in a diverse range of kinases, phosphatases, phospholipases, and cytoskeletal proteins, and bind left-handed polyproline type I1 helices (reviewed in Pawson, 1995).…”
mentioning
confidence: 99%
“…P40PhoX, p47phox, and p67phoX each contain Src homology 3 (SH3) domains, which mediate multiple associations with proline-rich targets within the NADPH oxidase complex (Fuchs et al, 1995;de Mendez et al, 1996). These domains are also present in a diverse range of kinases, phosphatases, phospholipases, and cytoskeletal proteins, and bind left-handed polyproline type I1 helices (reviewed in Pawson, 1995).…”
mentioning
confidence: 99%